Pendampingan Pelaku Usaha Mikro Berbasis Digital Melalui Pendaftaran Legalitas Usaha Menggunakan Sistem Online Single Submission (OSS) - Yuliana, Yuliana; Zuhro, Sania Maulida; Ratnasari, Aulia Putri; Ratnasari, Melania Dyah; Muflikah, Ellisa Nihayatul; Andriani, Andriani (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This community service is carried out using asset-based methods through the Asset-Based for Community Development (ABCD) program. The ABCD method is a model approach for the community to recognize its capacity or potential and use this capacity or potential to improve its standard of living and welfare. This mentoring activity was carried out for 30 microbusiness actors spread throughout the city of Kediri and across provinces. The micro-entrepreneurs who participate in the mentoring have a wide variety of business types, ranging from the food and beverage industry, receiving tailor-made clothing services, to trading. Assistance is carried out continuously for 30 working days.